2021
DOI: 10.7717/peerj.12287
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of diverse host infection mechanisms delineates an adaptive radiation of lampsiline freshwater mussels centered on their larval ecology

Abstract: North American watersheds contain a high diversity of freshwater mussels (Unionoida). During the long-lived, benthic phase of their life cycle, up to 40 species can co-occur in a single riffle and there is typically little evidence for major differences in their feeding ecology or microhabitat partitioning. In contrast, their brief parasitic larval phase involves the infection of a wide diversity of fish hosts and female mussels have evolved a spectrum of adaptations for infecting host fish with their offsprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 81 publications
(148 reference statements)
0
13
0
Order By: Relevance
“…Previous studies have also shown limited ability of mitochondrial DNA (mtDNA) to distinguish between members of the genus Elliptio (e.g., Inoue et al, 2018), suggesting further investigation is needed to determine whether mtDNA variation is insufficient to separate valid species or if taxonomic revision is warranted. Similarly, available mtDNA sequences show low interspecific divergence between L. cardium and L. satura ; however, a recent phylogenomic study using single‐nucleotide polymorphisms (SNPs) supported recognizing both as distinct, monophyletic taxa (Hewitt et al, 2021). The reliance of eDNA studies on comprehensive DNA libraries and accurate taxonomy amplifies the need for further refinement of unionid systematics and taxonomy; this was identified as the top issue in a national strategy for the conservation of native freshwater mussels by the Freshwater Mollusk Conservation Society (2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also shown limited ability of mitochondrial DNA (mtDNA) to distinguish between members of the genus Elliptio (e.g., Inoue et al, 2018), suggesting further investigation is needed to determine whether mtDNA variation is insufficient to separate valid species or if taxonomic revision is warranted. Similarly, available mtDNA sequences show low interspecific divergence between L. cardium and L. satura ; however, a recent phylogenomic study using single‐nucleotide polymorphisms (SNPs) supported recognizing both as distinct, monophyletic taxa (Hewitt et al, 2021). The reliance of eDNA studies on comprehensive DNA libraries and accurate taxonomy amplifies the need for further refinement of unionid systematics and taxonomy; this was identified as the top issue in a national strategy for the conservation of native freshwater mussels by the Freshwater Mollusk Conservation Society (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown limited ability of mitochondrial DNA (mtDNA) to distinguish between members of the genus Elliptio (e.g., Inoue et al, 2018), suggesting further investigation is needed to determine whether mtDNA variation is insufficient to separate valid species or if taxonomic revision is warranted. Similarly, available mtDNA sequences show low interspecific divergence between L. cardium and L. satura; however, a recent phylogenomic study using single-nucleotide polymorphisms (SNPs) supported recognizing both as distinct, monophyletic taxa (Hewitt et al, 2021).…”
mentioning
confidence: 99%
“…Timmermans et al (2020) used SNP data from Papilio dardanus to discover a genomic inversion associated with its mimetic polymorphism, and this approach is likely also tractable for Lampsilis fasciola given the availability of polymorphic broods – we are currently raising an additional polymorphic brood at the AABC. Mantle lures are a key adaptive trait in Lampsiline evolution and diversification (Hewitt, Haponski & Foighil, 2021) and Lampsilis fasciola is a promisinga highly tractable model system to uncover the genetics of lure development and variation in unionoid mussel.…”
Section: Discussionmentioning
confidence: 99%
“…The variability in lure display behavior among species of unionid is not well understood. Mimetic mantle lures predominate in Lampsilini, a major clade of North American freshwater mussels recently identified as a cryptic adaptive radiation centered on larval ecologies and specialized host-infection behaviors ( Hewitt, Haponski & Ó Foighil, 2021b ). This interaction is referred to as ‘cryptic’ because the specific host-parasite interactions are transient and difficult to determine in-situ .…”
Section: Introductionmentioning
confidence: 99%
“…Although mimetic mantle lures are a key adaptive trait of freshwater mussel diversification, the genetic regulators underlying their formation ( Kramer, 1970 ), variation ( Haag, Warren & Shillingsford, 1999 ; Zanatta, Fraley & Murphy, 2007 ; Barnhart, Haag & Roston, 2008 ), and evolution ( Zanatta & Murphy, 2006 ; Hewitt, Haponski & Ó Foighil, 2021b ) remain completely unknown. This gap in our knowledge is exacerbated by the stark conservation status of North American freshwater mussels, with two thirds of species classified as threatened or near-threatened ( Lopes-Lima et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%